1) если а = 1 , то х ∈ R
если а не равнo 1, то 0x=0 =>
2) если а = -1 , то 0x=0 => х ∈ R
если а ≠ -1, то
3) ax - 3 = x +3a
ax - x = 3a +3
(a-1)x = 3(a+1)
если а = 1 , то 0x=6 => х ∈ ∅
если а ≠ 1, то
Объяснение:
как то так
1) если а = 1 , то х ∈ R
если а не равнo 1, то 0x=0 =>![x =\frac{a-1}{1-a}](/tpl/images/1283/4018/03bb4.png)
2) если а = -1 , то 0x=0 => х ∈ R
если а ≠ -1, то![x = \frac{2a+1+a^2}{1+a}](/tpl/images/1283/4018/cd2d8.png)
3) ax - 3 = x +3a
ax - x = 3a +3
(a-1)x = 3(a+1)
если а = 1 , то 0x=6 => х ∈ ∅
если а ≠ 1, то![x=3\frac{a+1}{a-1}](/tpl/images/1283/4018/475d0.png)
Объяснение:
как то так